Nitrogen requirement and critical N content of stevia grown in two contrasting soils of Bangladesh - Maniruzzaman, Md; Chowdhury, Md Akhter Hossain; Mohiuddin, KM; Chowdhury, Tanzin (Research in Agriculture Livestock and Fisheries, 2016)
Nitrogen is recognized as one of the most limiting nutrient for crop growth in Bangladesh and can be supplemented with inorganic fertilizers like urea. The experiment was conducted in the net house of the Department of Agricultural Chemistry, Bangladesh Agricultural University during March to July 2012. The objective was to examine the effects of different levels of N on the growth, leaf biomass yield, N content and to estimate minimum N requirement and critical N content of stevia. The treatments included six N rates (0, 100, 150, 200, 250 and 300 kg ha-1). Plant sampling was done at 15, 30, 45 and 60 days after planting (DAP) to measure plant height, number of branches and leaves, fresh and dry weight of leaves, leaf area and N concentration. The results revealed that all the characters were significantly affected by different N rates. The highest values of all parameters except plant height and N concentration were obtained from 250 kg N ha-1 and the lowest values from N control. Nitrogen application at all levels increased leaf dry yield at harvest by 99 to 505% in acid soil and 69 to 438% in non-calcareous soil, respectively over control. The growth of most parameters was rapid at the later stages (30 to 60 DAP). Leaf N content proportionately increased with the increasing rates of N. The highest N concentration was obtained from its highest application (300 kg N ha-1). The minimum amount of N for maximum leaf biomass production in the plants grown in acid and non-calcareous soils was estimated to be ca 273 and 257 kg ha-1, respectively. The critical N concentration to achieve 80% of the maximum production of stevia leaf was also estimated to be ca 1.43 and 1.50% in the leaves of stevia plants grown in acid and non-calcareous soils, respectively Res. Agric., Livest. Fish.3(1): 87-97, April 2016